Evaluation of Sugarcane Families and Identification of Promising Families for Cane Yield and Juice Quality Traits in Early Selection Stages - Mallikarjun P. K., Sanjay B. Patil; Hanamaratti N. G., C. R. Patil, P. V. Patil (Archives of Current Research International, 2024)
The utilization of superior parental lines and identification of promising families enhance the genetic gain in sugarcane. To identify the promising families, 1620 progenies derived from twenty two crosses involving genetically diverse historical parents were evaluated for cane yield and juice quality attributing traits. The mean number of millable canes per clump (9.00), cane girth (2.32 cm), millable cane height (217.00 cm) and Brix% in juice (20.79%) were recorded. The significant variance, high broad-sense heritability and genetic advance over mean suggested that number of millable canes per clump, single cane weight, millable cane height, Pol% in juice and Brix% in juice are suitable for family evaluation. Based on progeny performance, families of Co 86032 × CoVC 14061 and Co 0312 GC, were found significantly superior compared to most popular clonal check, Co 86032 for number of millable canes per clump, similarly, CoVC 14062 × Co 89003 and Co 86002 × ISH 69 for cane girth, and CoVC 14062 × Co 89003, Co 11015 and Co 87015 for CCS% in juice content at early selection stages. Among 22 families studied, the four families viz., Co 86032 × CoVC 14061, CoVC 14062 × Co 89003, CoVC 14062 GC, Co 87015 GC and Co 11015 GC, produced higher percentage of population selection with acceptable range for commercially important traits (Brix% in juice, cane yield components). These identified promising families can be further exploited in sugarcane varietal improvement.